PATH ANALYSIS OF PERCEPTION OF HEAT PRESSURE, PULSE RATE, BODY TEMPERATURE AGAINST HEAT STRAIN EVENTS IN WORKERS IN BREM PRODUCTION INDUSTRY - Siska Wahyu; Sri Hernawati; Farida Wahyu Ningtyias (Journal of Vocational Health Studies, 2021)
Background: Brem industry workers can be at risk to get into heat strain in their workplace. The cases are caused by heat pressure, pulse rate, and body temperature. Purpose: To analyze the heat pressure, pulse rate, and body temperature that can influence the heat strain simultaneously to the workers of the Brem industry in the Kaliabu region, Madiun city, Indonesia. Method: The research is characteristic analytic observation quantitative with the cross-sectional approach in which a sample is 157 respondents with a total amount are 266 workers. The analysis test path use SPSS AMOS 23 accessories to analyze the data. Result: The results of the research are that heat stress does not influence the pulse rate (estimate 0, 02). Heat stress influences body temperature (estimate 0, 12). Heat stress does not influence the heat strain directly (estimate 0, 011). Pulse rate does not influence the heat strain (estimate 0, 08) and body temperature influences the heat strain (estimate 0, 04). Conclusion: Heat stress does not influence the heat strain directly but it influences the variety of body temperature so it needs to pay attention to the work duration time well. (7 hours working and 1 hour for taking rest). Also, it needed an arrangement of the room and adding the system of ventilation to get down the heat from the environment so heat strain can be restrained by checking the environment temperature and body temperature workers routine.